Rancang Bangun Aplikasi Manajemen Lagu Pada Radio Republik Indonesia (RRI) PRO 2 FM Surabaya - Ariocky Agustinus; Pantjawati Sudarmaningtyas; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Based on the primary functions of radio RRI (Radio Republik Indonesia) as the broadcast of music, where there are still many errors in the playback songs that are not in accordance with the rules and policies established by RRI Pro 2 FM. The subject matter is already made a determination and a standard rule in rotating track but in the implementation process track management is not going well because they MD (Music Director) less obey the rules that have been established, while the need for an arrangement of the song should be in accordance with the rules and daily needs of each event on broadcast activities. The resulting consequence is the ineffectiveness of the rules and affect the request or sms from radio listeners.The solution is to design management applications track PRO 2 FM. This application is able to facilitate MD in presenting or rotate songs with songs based on the rule of RRI PRO 2 FM so as to produce a daily or weekly playlist of songs that fit to the RRI PRO 2 FM. From the evaluation results can be concluded in this research is to produce applications that can help head of programming and Music Director in managing the song in order to avoid mistakes and have been able to meet the rules of the rotation track up to 100%.